Interferon Regulatory Factor-1 Mediates Alveolar Macrophage Pyroptosis During LPS-Induced Acute Lung Injury in Mice. Issue 3 (September 2016) - Wu, Dongdong; Pan, Pinhua; Su, Xiaoli; Zhang, Lemeng; Qin, Qingwu; Tan, Hongyi; Huang, Li; Li, Yuanyuan
Abstract : ABSTRACT: Previously, we demonstrated that pyroptosis in alveolar macrophages (AMs) plays an essential role in lipopolysaccharide (LPS)-induced acute lung injury. However, the underlying mechanism remains largely unclear. Here, we show that the absence of interferon regulatory factor 1 (IRF-1) in genetic knock-out mice strongly abrogates pyroptosis in AMs and alleviates the LPS-induced lung injury and systemic inflammation. Our study demonstrates that IRF-1 contributes to caspase-1 activation and apoptosis-associated speck-like protein containing a caspase activation and recruitment domain pyroptosome formation in AMs and leads to downstream inflammatory cytokine release, including that of IL-1β, IL-18, and HMGB1. The nuclear translocation of IRF-1 is linked to the presence of toll-like receptor 4 (TLR4). Our findings suggest that pyroptosis and the downstream inflammatory response in AMs induced by LPS is a process that is dependent on TLR4-mediated up-regulation of IRF-1. In summary, IRF-1 plays a key role in controlling caspase-1-dependent pyroptosis and inflammation.